Health care availability, quality, and unmet need: a comparison of transgender and cisgender residents of Ontario, Canada - Rachel Giblon; Greta R. Bauer (BMC, 2017)
Abstract Background Evidence suggests that transgender (trans) individuals in Canada are a medically underserved population; barriers range from lack of provider knowledge on trans issues to refusal of care. This paper provides the first formal estimation of health care inequalities between trans and cisgender individuals in Ontario, Canada. Methods Weighted statistics from the Ontario-wide Trans PULSE Project (n = 433) were compared with age-standardized Ontario data from the Canadian Community Health Survey (n = 39,980) to produce standardized prevalence differences (SPDs). Analysis was also conducted separately for trans men and trans women, each compared to the age-standardized Ontario population. Results An estimated 33.2% (26.4,40.9) of trans Ontarians reported a past-year unmet health care need in excess of the 10.7% expected based on the age-standardized Ontario population. Inequality was greatest comparing trans with cisgender men (SPD = 34.4% (23.0, 46.1). While trans Ontarians evaluated health care availability in Ontario similarly to the broader population, they were significantly more likely to evaluate availability in their community as fair or poor. Conclusions Trans Ontarians experience inequalities in perception and reported experiences of health care access, with 43.9% reporting a past-year unmet health care need.